Design estratégico feminista: uma proposta teórico-metodológica operada no contexto da cidade - Silva, Giulia Locatelli e (Universidade do Vale do Rio dos Sinos, 2023)
The patriarchal structure under which our society is organized reflects, in various spheres, its modes of oppression. The cities, the result of a construction governed by this paradigm, are a space where these impressions can be identified in the streets, buildings, and throughout their organizational system. This perception is even more evident when these influences are observed in the lives of women. Faced with this realization, strategic design presents itself as a potential methodological operator capable of transforming the reality of projects developed in this context with its dialogical and collective participation capabilities. However, just as in cities, one can perceive the influences of patriarchy on this field of study, which originated within and from this reality. Therefore, based on these observations and by connecting these factors, this study was born. The present research initially examines the ways in which the structure and planning of cities, built under a patriarchal context, interfere in the everyday lives of women. From this point, feminism is drawn upon as a field of study and knowledge under which new perspectives for the future and society can be constructed, understanding it as an epistemology capable of breaking with dominant design models, both in cities and, especially, in strategic design. Therefore, what is developed is the proposal of a feminist strategic design methodology, aiming to suggest and present new design perspectives capable of transforming the modes of operation and perception biases regarding design processes, taking into consideration, especially, the perspective of women. Through a journey guided by four operational verbs (listen, share, imagine and practice), adopting feminist ethical stances also represented by verbs (to be haunted, inquire, remember, celebrate, approach and care), the theoretical-methodological proposal developed is experienced and evaluated in a design context situated in Porto Alegre, in three different experiences, where the goal was to rethink the city and propose design alternatives that consider women's experiences.
Keywords: Design estratégico; Metodologia; Feminismo; Mulheres; Cidade; Strategic design; Methodology; Feminism; Women; City; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial